X-ray diffraction studies of onshore mud volcanoes in parts of the Upper Benue Trough, northeastern Nigeria - Musa, Ojochenemi K.; Kurowska, Ewa E.; Krzykawski, Tomasz; Onimisi, Jimoh A. (Geology, Geophysics and Environment, 2021)
The mineralogical studies of clay from the onshore mud volcanoes discovered in parts of the Upper Benue Trough of Nigeria provide a clue about the geological formation from which the extruded mud originates. The study area is a part of the Cretaceous Upper Benue Trough filled with Early Cretaceous continental deposits and Late Cretaceous marine deposits, having a history of magmatism dating from the Albian to the Pleistocene. The study approach involves integrated inorganic geochemical analysis of the samples to reveal their composition and origin. The results of XRD analysis of the fresh clays from the mud volcano revealed the presence of quartz, kaolinite, and other clay minerals (illite-smectite), feldspars, and in much lower quantities, other accessory minerals including muscovite, evaporites, calcite and dolomite, trona, barite, goethite. The saprolite samples are composed mainly of quartz, kaolinite, smectite-illite associations, and feldspars, traces of goethite, calcite, and evaporate minerals (sylvite, halite). The presence of calcite, dolomite, sylvite, and halite suggests the marine origin of the rocks, while trona mineral is a non-marine evaporate. The coexistence of these minerals in some of the analyzed samples suggests the deposition of sediments in a transitional environment of deposition. Traces of marine minerals are present in some of the samples but completely absent in others collected from another site. This suggests that the source rock formations from which the material originated are within the Upper Bima Sandstone interpreted as being deposited in a non-marine environment or the Yolde Formation, which is known as a transitional unit (transitional between the outcropping continental Upper Bima Sandstone and marine Pindiga Formation).